CODESRIA Bulletin Online, No. 9, September 2020 - The AfDB and Negotiating Finance Hegemonies: Journeying towards its Origins of Industrial Development and Regionalisation - Eka Ikpe - Eka Ikpe (CODESRIA Bulletin, 2020)
This article examines the African Development Bank’s (AfDB) engagement with industrial development and associated investment as part of continental integration across time, including under the leadership of Akinwunmi Adesina, who was first elected into post as President of AfDB in 2015 and re-elected for a second term in August 2020. In doing so, this article considers the significance and influence of foreign capital to the Bank’s work. Examining the control of finance offers some scope for analysing the US rejection of AfDB’s governance processes in the management of misconduct allegations against Adesina and the subsequent request for an externally driven process in June 2020. An independently led panel vindicated the AfDB governance process and Adesina in July 2020. The US is the second largest shareholder of the Bank after Nigeria. This concern with finance is pertinent and timely given the continental policy engagement on this theme.1 The AfDB was established in 1964, with the purpose of supporting economic and social development on the African continent. From its origins, larger economies played influential roles from Nigeria hosting the inaugural meeting in 1964 to Cote d’Ivoire hosting the Bank’s headquarters, with an interim 10year period, 2003–2013, relocation to Tunisia due to civil conflict in Cote d’Ivoire. Until 1972, the Bank’s membership included only independent African countries. Yet by 2015 its membership comprised all but Eritrea plus 23 nonregional members. The expansion of membership beyond African countries started in 1972 with nonregional lender members joining the African Development Fund (AfDF) and then the AfDB in 1982 (AfDB 2013). This expanded membership was arguably in recognition of the hegemonic control of finance by industrialised economies particularly in the global north although it also includes nonregional members in Asia and the Middle East. Broadening membership from regional to non-regional members was extensively contested. The result of such contentions included limitations to non-regional members’ votes and control to one-third within AfDB and half within AfDF. However, the debt crisis of the 1980s and 1990s and the Bank’s increasingly risky regional debtors forced an increased voice for non-regional lender members and raised their AfDB voting power to 40 per cent (Babb 2009: 31). These changes are noted as a critical juncture in challenging the hitherto influence of African members vis-à-vis nonregional lender members and the ‘increased surveillance by those outside that limited the extent to which the Bank could maintain an Africa-driven development agenda’ vis-à-vis the direction of global development policy (Mingst 2015: 82). The article continues with three sections as follows. First, it considers the theoretical arguments that have underscored the significance of industrial development for African transformation with emphasis on critical African perspectives. Second, it examines the AfDB’s trajectory of engagement with industrial development, particularly with attention to infrastructural investment and the ideological shifts that have underscored this. Third, it offers analysis of contemporary engagement with industrial development as interlinked with regionalisation with attention to the political economy dynamics of hegemonic control of finance. Here it also presents a brief case study on AfDB industrial infrastructural finance and the wider industrial development and potential regionalisation outcomes. Critical reflections on industrial development, regionalisation and finance for socio-economic transformation in Africa The theoretical argument for structural transformation and industrial change as central to development is rooted in classical development economic thought across structuralist and dependency schools. This approach underscored Africancentred considerations of socioeconomic transformation (Adesina 2020). It is concerned with the dynamic economies of scale of the manufacturing sector, the higher income elasticity of demand for manufactured goods (relative to the primary sector) and a particular aptitude for applying science and technology and novel approaches. Structuralists, for instance, have been clear on the need for capital investments to support industrial transformation and the design and creation of relevant institutions (Lewis 1954; Gerschenkron 1962; Rosenstein-Rodan 1946; Hirschman 1958). These salient arguments have endured but have been critiqued in various ways including for ignoring the structural and embedded inequalities within the global political economy that have entrenched the global south as suppliers of raw materials. Dependency theorists responded to the argument of structural inequalities in the global political economy by insisting that factors such as colonial legacies that spurred unequal patterns of exchange need to be disrupted to enable a drive towards industrial change. On this account, the Prebisch-Singer thesis offers up the argument for infant industry protection as necessary for altering terms of trade conditions that traditionally located global south and particularly African contexts as raw material exporters and higher value manufactured goods importers (Prebisch 1950; Singer 1950). Although diminished in some quarters, the school’s core arguments on the problem of unequal patterns of exchange in the global economy have prevailed. This is articulated in the contested negotiations of the European Union–Africa, Caribbean and Pacific Countries Economic Partnership Agreements, which have been regarded as reinforcing colonial terms of trade patterns that position African economies as exporters of primary products to Europe and importers of manufactured goods and services from Europe (Ikpe 2017). Critical political economist, Samir Amin, argued for a more radical restructuring of Africa’s engagement with the global economy. He proposed reprioritising internal mass markets and exchange as a basis for altering Africa’s interaction with the global economy (Amin 1974; 1987). He saw structural global inequality as connected also to other factors including technological dependence. Kvangraven (2019) shows the continued relevance of these ideas in the African context and beyond. Considering the limitations of quite small internal national markets on the African continent, regionalisation and regionalism would potentially offer an option for articulating a focus on internal, albeit regional and continental, markets. Claude Ake (1988: 160–161) clarified the significance of regional cooperation to provide a more robust base to negotiate with multinational corporations and international organisations and expand market size to facilitate industrial change. However, he offered a useful critique in the tendency of regionalism and regionalisation to prioritise interaction with the core, i.e. former metropoles at the expense of horizontal intra-African priorities citing the challenges between Francophone and Anglophone Africa. The co-opting of the planned ECOWAS Eco, by the Union économique et monétaire ouest africaine [West African Economic and Monetary Union], comprised largely of the Francophone former French colonies, to replace the hitherto CFA Franc in 2020 is another notable and contemporary case in point.2 This critique was also levelled at the operation of the New Partnership for African Development in entrenching unequal trade relationships and prioritising debt repayment (Taylor 2006; Adesina 2004). Ake (1988: 162) maintained that regional cooperation and development had the potential to underscore socio-economic transformation through product-sharing and rationalisation and high levels of economic policy coordination that could diversify and industrialise economic structures. These arguments were shared by the foremost voice on regionalisation in Africa, Adebayo Adedeji. He argued that regionalisation was imperative for challenging the impacts of ‘dispossession, colonisation, dependence and marginalisation’ (Adedeji 2002: 47). In the 1980 Lagos Plan of Action that he led, socio-economic transformation was to be based on regionalism and regionalisation as collective self-reliance, linked also to internally located industrial development (OAU 1980). Finance is of course critical to industrial policy and classical development economics theory articulates this in the significance of savings as well as complex institutional structures and systems for industrial development (Lewis 1954). Ikpe (2014) highlights the particular role that controlling finance has played in underscoring industrial policy and strategies in developmentalist approaches to development. Extending this idea to supranational contexts especially in global south spaces we can consider the emergence of regional and indeed continental systems for enabling access to finance for transformation. The Lagos Plan of Action articulated an important role for finance and strengthening the African Development Bank in national and regional industrialisation processes for investments, projects and technology acquisition (OAU 1980: 19, 21–22, 72). This reality underscored the impetus for establishing the Bank. The AfDB was consonant with the continent’s commitments to unity and self-reliance in the independence period exemplified also in the form of closed membership to African countries and in negotiations around more equitable representation of larger and smaller states at its inception (Barnes 1984: 152; Ebong 1974: Ch 3). Beyond Africa, Helleiner (2019) reflects on historical systems of multilateral development finance in Asia and Latin America to underscore visions of such structures as anti-imperialist. Locating the significance of finance for development within debates on unequal patterns of exchange, Amin (2014) was clear on the challenge of access to finance in peripheral contexts due to the dominance and control of the global north in this sphere. The interactions between the AfDB and key actors in the core, such as the US, are of concern at this juncture. Park (2017) notes how the US has consistently used its power of the purse as a majority shareholder to steer other donor shareholders to multilateral development banks to accept its position on accountability including through threats to withhold funds. She notes how the US sought to halt the AfDB’s role in providing a financial lifeline to economies greatly impacted by the debt crises by withholding contributions to ensure it prioritised its financial viability over supporting African member states in crisis. Although Park (2017) treats accountability as a benign and apolitical, Cornwall and Brock (2005) remind us that development policy buzzwords, including accountability, are anything but benign. Rather by postulating them as the norm they are ‘reduced to monochrome; while they may be filled with other meanings when deployed in other contexts, by other actors, their appearance as consensus neutralises dissonant elements’ (Cornwall and Brock 2005: 1047). They emphasise the neoliberal underpinning, and therein, market– fundamentalist interpretations of these terms as the norm. Essentially what seems to be at play is the contention between the priorities of borrower members of AfDB and similar multilateral development banks and priorities of non-regional lender members. In fact, Humphries (2019) finds that within multilateral development banks, borrower members can be more flexible in operational terms but suffer in terms of access to finance. This reinforces the significance of lender members and their hegemonic control of access to finance and the risk of contending priorities and attendant challenges faced by development banks in the developing world. Charting the AfDB’s interactions with industrial development via infrastructural investment as part of regional development AfDB’s role in finance provision for industrial progress has historically been anchored on support to infrastructural development. This was linked to the need to address the reality of disarticulated infrastructural systems that accompanied colonisation (Ake 1988: 38). At its inception, there was an element of pragmatism to the Bank’s agenda, given its limited capital base. Barnes (1983: 159) highlights the AfDB’s communication of its credibility through focus on ‘bankable’ projects, i.e. infrastructural investments that would generate a return. The Bank’s support was characterised initially by focus on influential polar countries often with the strongest economies and industrial trajectories as opposed to regional priorities. Barnes (1983) and Ebong (1974) show that, in its first seven years, loan commitments were largely made to Algeria, Cote d’Ivoire, Kenya and Nigeria. This expanded to include larger regional projects. In West Africa, the AfDB supported projects including the Mano River Union Bridge, the Régie du chemin de fer Abidjan– Niger and the Diama Dam Project (Barnes 1983). Over time, other loan facilities including the AfDF and the Nigerian Trust Fund were established that were better able to engage social development priorities and a wider range of beneficiary countries. With transitions within global development policy moving away from structuralist towards more market–fundamentalist approaches, the Bank’s practices evolved as well. AfDB’s support steered borrower states on policies such as ensuring evidence of profitability in ways that included charging consumers market prices and forbidding borrowers from undertaking other infrastructural commitments that risked the returns to the Bank (Mingst 1990: 72). In some ways this departed from the structuralist ‘Big Push’ agenda in infrastructural investment to drive industrial development. While there has been consistent recognition of the commitments to the Lagos Plan of Action, wider global development policy has been influential to the AfDB’s approach. The World Bank articulated an expectation that the AfDB would support it in driving policy reform on the continent (Mingst 2015; World Bank 1985). Indeed, former US Executive Director of the AfDB, Sherk has noted how loan performances were monitored interchangeably by the World Bank and the AfDB (US Government, 2001). This period of subscription to global development policy agendas is evidenced also by the AfDB co-financing 80 per cent of its projects through the World Bank over the 1990s with subtle policy pressures from the latter (Babb 2009: 152; Mingst 1990: 73). The AfDB has seen transitions across periods, from its history as having a fiercely African character and ideological commitment to industrial development coupled with infrastructural investment support to the contended opening up to non-regional members within AfDB alongside focus on profitability and responsiveness to shareholders. This transition was accompanied by a move from project support to advice and programme support in adaptation to global development policy directions. This shift also implied tensions between increased attention to national concerns as opposed to seemingly complex regional agendas (Mingst 2015). In contemporary times, industrialisation is finding space again as a central element of development policy. Long-term advocate of industrial development, Ha Joon Chang, draws attention to this shift in discourses (Chang and Andreoni 2020). This follows the neglect of industrial policy that accompanied the structural adjustment period as well as the poverty reduction strategy debates (Mkandawire 2010). Arguably, former World Bank chief economist Justin Lin’s new structural economics has served a role in this shift in the mainstream, while remaining committed to a market fundamentalist approach with reliance on static comparative advantage. On the African continent, there is rising attention to industrialisation in policy circles at the continental level. From 2013 to 2017, UN Economic Commission for Africa Economic Reports on Africa focused distinctly on industrialisation as central to socioeconomic change. This global development policy direction occurs also at a time when much has been made of the African continent’s emergence and high growth levels. GDP growth in Africa between 2000 and 2011 averaged 5 per cent and GDP growth for ten African countries, namely, Equatorial Guinea, Angola, Sierra Leone, Nigeria, Ethiopia, Rwanda, Chad, Mozambique, Uganda and Tanzania stood at 9 per cent (World Bank 2020). Yet the failings of industrial progress as part of this story and the overwhelming significance of resource exports and therein larger economies has been a point of reckoning around the continent’s reinforced position as a supplier of raw materials (Moghalu 2014; Taylor 2016). Indeed, the resource price collapses in 2015 challenged the “Africa rising” narrative and the place of larger economies, including Nigeria that was in recession in 2016 and Angola that has remained in recession ever since (World Bank 2020). The flipside of the narrative has been non-net mineral and fuel resource exporters that have shown resilience through the crisis alongside improving levels of structural change. These include Ethiopia, Cote d’Ivoire and Rwanda that have averaged 9 per cent, 8 per cent and 7 per cent GDP growth rates over 2012–2019, respectively (World Bank 2020). In the case of Ethiopia, manufacturing value added growth doubled from 7.2 per cent over 2000–2011 to 15.2 per cent over 2012–2019 (World Bank 2020). In the end even resource exporters are beginning to show increasing levels of manufacturing value added with Nigeria going from 3.2 per cent to 5.9 per cent over the periods of 2000–2011 to 2012–2019 (World Bank 2020). Such patterns are not necessarily altering the structure of Gross Domestic Product. In Nigeria and Ethiopia, manufacturing value added as a percentage of GDP, has retained similar averages over the two decades at 4.8 per cent and 9.9 per cent, respectively (World Bank 2020).3 Significantly, this period has also been accompanied by intracontinental trade patterns that are more diverse than extracontinental trade. UNCTAD (2019: 23–25) shows that the continent’s global exportsconstitute only 20 per cent of manufactures due to the concentration in minerals and fuels vis-à-vis 45 per cent of manufactures as a proportion of intra-African exports. This contextual picture clarifies the background to the reenergised commitment to the place of regionalism and regionalisation through economic and trade integration with the African Continental Free Trade Area (AfCTA). The AfCTA is intended to align industrial policy to trade policy on the continent and in doing so create the largest single market globally of 1.3 billion people and a joint GDP of 2.2 trillion USD (UNCTAD 2019: 6; xiii).4 It is premised on: discouraging the exports of raw materials; privileging intracontinental trade, with higher proportions of manufactured exports to encourage industrial upgrading; and providing a larger collective base for extracontinental manufactured exports. It has not been without challenges including concern about national industrial policy priorities due to local domestic production capacity problems. In this regard Nigeria has been circumspect in its commitments; it has signed the agreement but is yet to ratify it, owing to factors including concerns from local manufacturers (NESG 2019). Negotiating finance in a seeming return to infrastructural investment and industrial development AfDB appears to be returning to a version of its historical agenda of regional integration and infrastructural investment and its leadership role on the continent (AfDB 2013: 14–15). This is purposed around infrastructural investments that may support larger more attractive African markets, improved intracontinental trade and extracontinental exports. Mingst (2015) articulates its more systematic approach in this regard. The Bank is clear on priority areas of infrastructure and regional integration. In particular, links are drawn to the potential outcome of infrastructural investment, green growth and participation in global value chains (AfDB 2013). These are influenced continually by global development policy narratives including improving profitability and competitiveness and emphasis on enabling private sector leadership. There are pertinent notes of caution on the demerits of participation in global value chains particularly at lower ends of value chain (Ghosh 2019). Under President Adesina, AfDB has been forthright about the commitment to infrastructural development and regional integration with a concerted focus on industrial transformation. This agenda has also been attentive to the challenges associated with the continent’s participation in the global value chains especially in lower value activities. Its five developmental priorities include an ‘Industrialize Africa’ agenda that is concerned with domestic manufacturing that utilises local raw materials and develops linkages with intracontinental and global production networks (AfDB 2019a). This is alongside a regional integration priority, ‘Integrate Africa’, that is built upon regional infrastructural investment within programmes including the African Union Programme for Infrastructural Development in Africa, with special attention to energy, transport and communication and economic integration, with the AfCTA, and particular focus on the potential of the continent’s consumer market (AfDB 2019b). The Bank’s direction has been important in driving commoditybased industrialisation and the development of forward and backward linkages with potential for strengthened economic and trade integration. An important exemplar is one of the AfDB’s flagship projects of an investment loan totalling 100 million USD to the Indorama Eleme Petrochemicals plant in Rivers State, Nigeria to support the development of a gas to fertiliser plant to address domestic and regional demand (AfDB 2019a; AfDB 2012; IFC 2019).5 This investment extends existing structural transformation in the use of gas for downstream production of manufacturing inputs, olefins, polypropylene and polyethylene that have been significant to industrial development including for consumable plastics (AfDB 2012). On this note, Indorama Eleme is building forward production linkages with the budding medical supplies manufacturing sector. In neighbouring Akwa Ibom State, the Jubilee Syringes manufacturing firm, established in 2017, reports its use of polypropylene from Indorama Eleme Petrochemicals (Nsinene 2019; Ukpong 2019). The factory is the largest in Africa with the potential for and commitments to addressing domestic market needs and exports to the subregion and the wider continent and beyond given its production capacity of 350–400 million syringes per annum (NIPC 2017). These dynamics have been underscored by complex interactions across the state and the market, particularly foreign private capital. First Jubilee Syringes benefits from industrial policy defined by tax breaks as well as import substitution policies such as increased tariffs on imported syringes from 5 per cent to 70 per cent in 2018; notably polypropylene tariff rates remain unchanged (Deloitte 2018). Second there has been a central role for foreign capital in the global south with Indonesian–Singaporean capital in Indorama Eleme Petrochemicals and Turkish capital for Jubilee Syringes. The increasing roles for foreign capital from the global south, with attention to industrial and trade policy and the role of the Bank suggest a broadening of significant actors, particularly in the control of finance for industrial development. It is useful to consider the implications this may have for traditional global finance hegemons’ interactions with AfDB. In this regard, while the US dismissal of AfDB governance processes has been presented as an exercise in building norms it has also been seen as a response to the Bank’s evolving interactions with key global emerging economies in support of an African developmental agenda. Against this background, the use of norm-setting narratives in development banks in relation to changing international political economy realities is pertinent. Former US Executive Director of the AfDB, Sherk, reported to the US House of Representatives as follows, ‘Suffice it to say that the countries most adept at seeing their objectives incorporated into MDB [multilateral development banks] operational guidelines are those that focus their objectives narrowly, stay informed of bank policies and procedures on a day-to-day basis, and successfully lobby other shareholding countries in support of the objectives that they favor’ (US Government 2001). Yet regional members can set about challenging the assertions by finance hegemons and what actually constitutes norms. In a joint statement, former African Heads of State have been forthright on the need for the US to abide by the rules and procedures of the AfDB governance system, as the institution’s norms. They note that ‘no nation, regardless of how powerful, has a veto power’ potentially to alter such norms.6 Significantly the agreement between the independently led panel and the AfDB governance process potentially reinforces the position of the African leaders in the robustness of AfDB processes (Oyero 2020). More generally contemporary emerging economies are noted as attempting also to challenge US hegemonic control of finance. Xu (2016: 228–257) argues that Chinese commitments to the New Development Bank and the Asian Infrastructure Investment Bank are intended to challenge US control of finance in development. Runde, Senior Vice President of the Centre for Strategic and International Studies, has described the US challenge to Adesina as a disruption by the Trump administration that is a ‘good tactic and a poor strategy’, suggesting that this has political undertones (BBC 2020). While challenging the timing of this intervention in relation to the pandemic, Professor Nancy Birdsall, alludes interestingly to the need for the AfDB to consider additional prominent members such as China (BBC 2020). In doing so, she raises the need to challenge the US hegemonic influence and what Babb (2009: 41) terms its donor leverage. In an attempt to influence the US position, the inaugural US Executive Director at the AfDB, Doley, had articulated support for Adesina’s re-election on account of the vibrant role of the Bank in supporting African transformation particularly in driving infrastructural development (Doley 2020). Notably he downplays concerns about global south powers in Africa, specifically China, and rather asserts US hegemonic influence as significant to the global economy. Given the outcome of the independent investigation that has vindicated the AfDB process, this is potentially a new juncture that politically challenges the US as a finance hegemon; it is left to see whether there will be a counter response that more explicitly deploys donor leverage. As Mingst (1990: 119) suggests, hegemonic donor members can indeed have the opportunity to wield power and dictate the terms of development banks. Babb (2009: 37, 31) is also clear that the US is an activist shareholder of multilateral banks where it uses threats of withholding resources to drive its policy agenda. Assertions have been made about particular leanings of political constituencies such as the Republican critique of US engagement with multilateral banks as not sufficiently driving US security interests vis-à-vis bilateral aid (Babb 2009: 87). Within this context, the AfDB walks a tightrope between prioritising articulated African economic interests and serving non-regional, powerful and influential shareholder and financial capital interests. Adesina has been forthright about the Bank’s role in supporting regional integration as part of industrialisation alongside actively courting a wide range of global finance actors. Such prioritisation may not bode necessarily well for the Bank’s non-regional shareholders that are perhaps more focused on the attendant dividends and potential risks. This is an expected dilemma that accompanies the Bank’s capacity to balance a developmental and transformational agenda, the increasing relevance of capital from emerging economies with access to hegemonic finance that is in many ways dominated by the traditional metropoles. Regardless of the underpinning of the US response to AfDB’s governance process what is clear is the hegemonic power it wields to the Bank’s functioning and therein its actions and efforts towards the continent’s socio-economic transformation. In the end, Samir Amin’s arguments about the significance of the source and control of finance for Africa’s developmental agenda remain relevant, pertinent and instructive for how it negotiates and challenges its positioning in the global economy. The experiences of this episode of resistance to the US challenge to the AfDB’s norms suggest tentatively that there is some scope to negotiate and uphold commitment to an African way. Notes The UN Economic Commission for Africa asserts this with its 2020 Report focused on ‘Innovative Finance for Private Sector Development in Africa’. This agreement was undertaken and implemented between WAEMU countries and France to the chagrin of Anglophone ECOWAS member states as it leaves the Eco pegged to Euro and backed by the French Treasury (M’Bida et al. 2020). Services have experienced more extensive expansion in output across the continent in at least 45 countries including in Ethiopia and Nigeria (UNCTAD,2015: 1213). Adesina (2020) also notes this trend. As at July 2020, it has had 54 signatories and 28 ratifications. This investment is alongside other sources of international finance from Nigeria, global south and global north contexts. Press statement by concerned African leaders, “ Leadership of the African Development Bank: A Need for Caution” May 29, 2020. https://allafrica.com/view/resource/main/main/ id/00130033.html